2017
DOI: 10.1002/marc.201700303
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Novel Microporous Dihydroxyl‐Functionalized Triptycene‐Diamine‐Based Polyimide for Natural Gas Membrane Separation

Abstract: An intrinsically microporous polyimide is synthesized in m‐cresol by a one‐pot high‐temperature condensation reaction of 4,4′‐(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and newly designed 2,6 (7)‐dihydroxy‐3,7(6)‐diaminotriptycene (DAT1‐OH). The 6FDA‐DAT1‐OH polyimide is thermally stable up to 440 °C, shows excellent solubility in polar solvents, and has moderately high Brunauer‐Teller‐Emmett (BET) surface area of 160 m2 g−1, as determined by nitrogen adsorption at −196 °C. Hydroxyl functionalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 37 publications
(58 reference statements)
0
31
0
Order By: Relevance
“…7,8 To reach this objective, the incorporation of polar functionalities in the polymer backbone, such as hydroxyl (-OH) and carboxyl (-COOH) groups were demonstrated by Stern's group and confirmed by others for low-free-volume polyimides with CO 2 /CH 4 permeability selectivities significantly higher than those of similar non-functionalized polyimides and 2 to 3 times higher than that of commercial cellulose triacetate. [9][10][11] Our group applied this approach by introducing hydroxyl-functionalization to various PIM-PIs, such spirobisindane [12][13][14] , spirobifluorene 15 , triptycene [16][17][18][19] and Tröger's base. 20 Wang et al recently reviewed PIM-PIs reported in the literature and found that OH-functionalized PIM-PIs are among the most promising membrane materials for CO 2 removal from natural gas with performance located on the 2018 mixed-gas CO 2 /CH 4 upper bound.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7,8 To reach this objective, the incorporation of polar functionalities in the polymer backbone, such as hydroxyl (-OH) and carboxyl (-COOH) groups were demonstrated by Stern's group and confirmed by others for low-free-volume polyimides with CO 2 /CH 4 permeability selectivities significantly higher than those of similar non-functionalized polyimides and 2 to 3 times higher than that of commercial cellulose triacetate. [9][10][11] Our group applied this approach by introducing hydroxyl-functionalization to various PIM-PIs, such spirobisindane [12][13][14] , spirobifluorene 15 , triptycene [16][17][18][19] and Tröger's base. 20 Wang et al recently reviewed PIM-PIs reported in the literature and found that OH-functionalized PIM-PIs are among the most promising membrane materials for CO 2 removal from natural gas with performance located on the 2018 mixed-gas CO 2 /CH 4 upper bound.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The commercial dianhydrides 4,4′‐hexafluoroisopropyliden diphthalicanhydride ( 6FDA ) and pyromellitic anhydride ( PMDA ), were selected with the purpose to produce polymers with even higher structural rigidity than these supported by the presence of ( 5 ). 6FDA has received much interest because most of their PIs have exhibited good gas separation performances compared to other polyimidic materials . In this work, the relationship between the PI structures and their solubility, and thermal stability and properties of gas transport, was reported.…”
Section: Introductionmentioning
confidence: 95%
“…PI-PIMs are generally divided into three categories: 1) PIMs made from reaction of dianhydride with contortion sites, such as SBI, EA and Trip, and halogen-containing aromatic diamines without contortion sites [32][33][34][35][36]; ii) PIMs prepared through dianhydride without contortion sites but diamines with contortions sites, such as SBI, TB, Trip, and pentiptycene [37][38][39][40][41][42][43][44]; iii) PIMs formed via TB polymerization of single di-amino aromatic monomer with imide bonds and contortion sites [45][46][47]. PI-PIMs with contorted sites in both dianhydride and TB-based diamine units were seldom reported [48].…”
Section: Polyimide-based Pimsmentioning
confidence: 99%